Trematodes of family Opecoelidae in Central Part of Svalbard - Otáhal, Ondřej (Jihočeská univerzita, 2015)
This study provides results of morphological analyses of material from the fish species Myoxocephalus scorpius and Gymnocanthus tricuspis from Svalbard. Adults of Podocotyle atomon were studied using carmine stain (inner structures) and scanning electron microscopy for viewing surface structures. Experimental infection of an intermediate host (Amphipoda) in the natural environment was documented during a field trip to Svalbard. Based on these findings, the life cycle of Podocotyle atomon was complemented.
Trematodes of family Opecoelidae in Central Part of Svalbard
Keywords: motolice; svalbard; podocotyle; opecoelidae; podocotyle atomon; podocotyle reflexa; Opecoelidae; Podocotyle atomon; morphological analyses; experimental infection; Svalbard; podocotyle reflexa